2016
DOI: 10.1016/j.addbeh.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Sexual revictimization, PTSD, and problem drinking in sexual assault survivors

Abstract: Posttraumatic stress disorder (PTSD) and problem drinking are common and often co-occurring sequelae experienced by women survivors of adult sexual assault, yet revictimization may mediate risk of symptoms over time. Structural equation modeling was used to examine data from a 3-wave panel design with a large (N = 1,012), ethnically diverse sample of women assault survivors to examine whether repeated sexual victimization related to greater PTSD and problem drinking. Structural equation modeling revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 24 publications
(30 reference statements)
5
59
0
5
Order By: Relevance
“…We found that women who had been revictimized during the 3-year study reported greater problems than those who had not. This effect remained when CSA history was controlled for, which also contributed to greater symptoms, consistent with previous literature on the topic (Ullman et al, 2005; Ullman et al, 2009). These results suggest that multiple sexual victimizations in adulthood therefore have additive effects in terms of survivor psychological outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…We found that women who had been revictimized during the 3-year study reported greater problems than those who had not. This effect remained when CSA history was controlled for, which also contributed to greater symptoms, consistent with previous literature on the topic (Ullman et al, 2005; Ullman et al, 2009). These results suggest that multiple sexual victimizations in adulthood therefore have additive effects in terms of survivor psychological outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that other factors than social reactions were more important predictors of drinking. Similar to previous adult sexual assault studies, maladaptive coping was related to greater alcohol consumption and problem drinking (Ullman et al, 2005). A possible explanation for this result is that maladaptive coping includes substance use coping.…”
Section: Discussionsupporting
confidence: 81%
“…Avoidance coping strategies are a common response to stressful life events, such as rape (Littleton, Horsley, John, & Nelson 2007). Women with histories of sexual victimization and other traumas (e.g., child abuse, IPV) may be more likely to engage in various forms of avoidance or maladaptive coping such as drinking to cope (Bissonnette et al, 1997; Ullman, Filipas, Townsend & Starzynski, 2005). Drinking to cope with distress is related to greater alcohol consumption and drinking problems (Holahan, Moos, Holahan, Cronkite, & Randall, 2001; Park & Levenson, 2002).…”
mentioning
confidence: 99%
“…Further, this study excluded women who reported behaviors consistent with problem drinking, and these findings may not generalize to light drinkers, abstainers, or women meeting criteria for alcohol use disorder. Sexual assault is associated with problem drinking (Griffin, Wardell, & Read, 2013; Ullman, 2016). Because problem drinkers were excluded, we are cautious in the applicability of these results to all survivors of sexual assault.…”
Section: Discussionmentioning
confidence: 99%